Ethical and bioethical stances of John Paul II - Ciszek, Mariusz (Studia Ecologiae et Bioethicae, 2008)
John Paul II has left behind a huge legacy of social teaching which retain its value till the present days therefore it is worth to remind the readers his significant ideas. In my article I familiarized readers with stances of John Paul II related to specific issues on medical ethicists and ecological aspects of human life protection based upon papal encyclicals, the article consists of two main parts: first refers to pope’s bioethical stances existed in encyclical Evangelium vitae (1995); the second one presented pope’s thoughts on environmental protection which could be find in the following encyclicals: Redemptor hominis (1979); Sollicitudo rei socialis (1987); Centesimus annus (1991) - and again in - Evangelium vitae (1995).